HUBUNGAN TINGKAT STRES DENGAN PERKULIAHAN BERBASIS DARING TERHADAP KUALITAS TIDUR MAHASISWA SEMESTER AKHIR SARJANA KEDOKTERAN PADA BEBERAPA UNIVERSITAS DI JAKARTA TAHUN AJARAN 2021/2022 SELAMA PANDEMI COVID-19 - Alicia Kartika (2022)
The outbreak of COVID-19 has had many impacts on various sectors of life throughout the world. One of the behaviors that have changed in the education sector in Indonesia is organizing all online-based learning activities from home. Changes that occur suddenly and drastically have made a significant impact on the stress levels and sleep quality of medical students, especially those who are in their final semester. The purpose of this study is to determine and illustrate the level of stress, the quality of sleep, and the relationship between these two variables. This study was a cross-sectional study. The stress level was assessed using the Depression Anxiety Stress Scale-21 (DASS-21) questionnaire and the Pittsburgh Sleep Quality Index (PSQI) questionnaire to assess sleep quality. Questionnaires that were fully filled were analyzed using Spearman correlation test with SPSS 22. As a result, of the 260 students from 11 universities in Jakarta, there were 162 students (62.3%) who suffered from mild to very severe levels of stress, and 165 students (63.4%) who experienced poor quality of sleep. The results of the statistical test and the Spearman rank correlation showed a significant and very strong correlation between the level of stress on the quality of sleep with p < 0.05 and r = 0.824. In summary, it may be concluded that medical students have a high prevalence of stress levels, poor sleep quality and there is a significant association between level of stress and sleep quality. Therefore, it is necessary to take preventive measures to reduce stress, which also improves the sleep quality of students.